2020
DOI: 10.12688/f1000research.22341.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the epidemiology and prevention of Streptococcus pneumoniae infections

Abstract: The introduction of pneumococcal conjugate vaccines (PCVs) 7 and 13 into national childhood immunization programs in the US in 2000 and 2010, respectively, proved to be remarkably successful in reducing infant mortality due to invasive pneumococcal disease (IPD), resulting in widespread uptake of these vaccines. Secondary herd protection of non-vaccinated adults against IPD has proven to be an additional public health benefit of childhood immunization with PCVs, particularly in the case of the vulnerable elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 77 publications
0
30
0
2
Order By: Relevance
“…The emergence of multidrug-resistant S. pneumoniae strains has increased the mortality and morbidity associated with pneumococcal infections ( Van Bambeke et al, 2007 ). Available pneumococcal vaccines such as the polysaccharide vaccine or the pneumococcal conjugate vaccine provide insufficient immunization ( Feldman and Anderson, 2020 ). Taken together, S. pneumoniae is responsible for approximately 40,000 deaths per year in the United States alone ( Brooks and Mias, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of multidrug-resistant S. pneumoniae strains has increased the mortality and morbidity associated with pneumococcal infections ( Van Bambeke et al, 2007 ). Available pneumococcal vaccines such as the polysaccharide vaccine or the pneumococcal conjugate vaccine provide insufficient immunization ( Feldman and Anderson, 2020 ). Taken together, S. pneumoniae is responsible for approximately 40,000 deaths per year in the United States alone ( Brooks and Mias, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PPSV23 includes 23 serotypes of pneumococci polysaccharides, which stimulate the immune system to produce antibodies [ 15 ]. Unconjugated polysaccharide vaccines induce a T‐cell response, without the establishment of B‐cell memory while conjugated polysaccharide vaccines as well as inducing T-cell response also establish B-cell memory that ensures long- term immunization effect [ 16 19 ]. Different studies have shown that more than 80% of healthy adults who receive PPSV23 develop antibodies against the serotypes contained in the vaccine; the immune response usually occurs within 2 to 3 weeks after vaccination in adults.…”
Section: Introductionmentioning
confidence: 99%
“…As of 2016, 59 countries did not have the pneumococcal vaccine in their childhood immunisation schemes. Access to vaccines in most LMICs has been limited by cost but this challenge has been addressed by GAVI, the Vaccine Alliance which has sponsored the pneumococcal vaccine in 54 countries (21,22). Given otitis has been identified to be the most prevalent predisposing factor to intracranial suppurations across LMICs, it may also be possible to reduce intracranial suppurations by promptly treating otitis with effective antibiotics.…”
Section: Discussionmentioning
confidence: 99%